ESTIMATION OF POSITION ERROR IN A DUAL-FREQUENCY IRNSS USER-RECEIVER OVER BANGALORE REGION - Md. Tosicul Wara, M. S. Bhuvaneshwari, M.R. Raghavendra & U. N. Vasantha Kumari (International Journal of Research Science and Management, 2019)
In satellite based navigation systems (such as GPS, the Global Positioning System or IRNSS, the Indian Regional Navigation Satellite System), unlike a single-frequency user-receiver, the dual-frequency user-receiver doesn’t require the appropriate ionospheric models for correcting the range error due to ionospheric propagation. Instead, in such dual-frequency receiver, the ionospheric range error of the observed satellite is computed in terms of the difference between the measured pseudo-ranges at two operating carriers of the satellite. Consequently, in such receiver, the ionospheric range error estimation will be more accurate, because the contribution to the range error due to all the frequency independent error-sources will be nullified while taking the difference between the two measured pseudo-ranges. However, in such dual-frequency receiver, the ionospheric range error estimation will be perturbed by the presence of several frequency dependent errorsources. In this paper an algorithm has been formulated to estimate the position error of a dual-frequency IRNSS user-receiver over the Bangalore region.